Performance of scintillating tiles with direct silicon-photomultiplier (SiPM) readout for application to large area detectors. (27th January 2022) - Balla, A.; Buonomo, B.; Cafaro, V.; Calcaterra, A.; Cardelli, F.; Ceccucci, A.; Ciambrone, P.; Cicero, V.; Di Giovenale, D.; Di Giulio, C.; Felici, G.; Foggetta, L.G.; et al.
Abstract: The light yield, the time resolution and the efficiency of different types of scintillating tiles with direct Silicon Photomultiplier readout and instrumented with a customised front-end electronics have been measured at the Beam Test Facility of Laboratori Nazionali di Frascati and several test stands. The results obtained on minimum ionising particles with different detector configurations are presented. A time resolution of the order of 300 ps, a light yield of more than 230 photo-electrons, and an efficiency better than 99.8% are obtained with ∼ 225 cm 2 large area tiles. This technology is suitable for a wide range of applications in high-energy physics, in particular for large area muon and timing detectors.